The Impact of COVID-19 on Neurology Education: A Medical Student Perspective - Guadix, Sergio W.; Sha, Carrie; Sandrone, Stefano; Safdieh, Joseph E.; Sarva, Harini (Frontiers in Education, 2020)
The COVID-19 pandemic has fundamentally altered the pre-clerkship, clerkship, and research experiences for medical students. Although these changes impact all specialties, we highlight the unique challenges faced by neurology education and discuss methods by which our institution is adapting to these changes at the epicenter of the pandemic in the U.S. We include a few examples of how some neurology departments around the country have altered their teaching methods in the COVID-19 era and capitalize on lessons learned by proposing new strategies for moving neurology education forward.